Zymosan-induced luminol-dependent chemiluminescence response of circulating and extravasated leukocytes in experimental sepsis. Issue 2 (2004) - Khan, Haseeb Ahmad
Abstract : This study examines a concurrent profiling of circulating and extravasated polymorphonuclear leukocytes (PMNs) in a rat model of experimental sepsis. Fecal peritonitis was induced in Wistar male rats by intraperitoneal instillation of a fecal suspension in saline (1:1 w/v). Blood and peritoneal fluid were collected 8 h following fecal inoculation for the evaluation of inflammatory response of PMNs using zymosan-induced luminol-dependent chemiluminescence. Fifty microliters of pre-diluted blood or peritoneal fluid samples were mixed with 150 μl of reaction mixture (4×10 −4 M luminol+50 μg opsonized zymosan+0.1% gelatin in Hank's balanced salt solution) and the chemiluminescence signal was measured in a luminometer at 37˚C. Fecal peritonitis caused a significant leukocytopenia (3540±297 mm−3 versus control value of 7525±711 mm −3, p < 0.001 ) accompanied by massive infiltration of PMNs in the peritoneal cavity (34700±4006 versus 7325±425 mm −3, p < 0.001 ). The phagocytic activity of circulating blood PMNs was down-regulated whereas a significant up-regulation was observed in the activity of PMNs from peritoneal fluid. In conclusion, this study clearly demonstrates sepsis-induced alterations in both blood and peritoneal fluid PMNs and their quantitative assessment may be helpful in disease evaluation and designing effective therapies.